Robotic‐assisted percutaneous coronary intervention in a COVID‐19 patient. Issue 3 (20th May 2020) - Tabaza, Luai; Virk, Hafeez ul Hassan; Janzer, Sean; George, Jon C.
Abstract: Coronavirus disease‐2019 (COVID‐19) pandemic is the biggest global health threat in the 21st century. We describe a case of a patient with suspected COVID‐19 who needed urgent coronary artery interrogation, in which we utilized robotic assistance to minimize the risk of exposure to COVID‐19 and reduced personal protective equipment needed by the procedural team.